2014
DOI: 10.4050/jahs.59.022008
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Studies on a Micro Air Vehicle–Scale Cycloidal Rotor

Abstract: Systematic wind tunnel measurements were conducted on a small-scale cycloidal rotor (cyclorotor) with a span and diameter of approximately 15 cm. The three parameters varied in the studies were the blade pitch amplitude, phasing of blade pitch with respect to the freestream direction, and advance ratio. The measured quantities included the rotor lift, propulsive force, and power. At low advance ratios, both pitch amplitude and phase angle were effective in varying the rotor lift and propulsive force. At high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Systematic forward flight studies were also conducted in the wind tunnel, which showed the potential for a cyclorotor to perform efficient high-speed forward flight even beyond an advance ratio of 1.0 by a simple phasing of the cyclic blade-pitch schedule. 6,14 As shown in Figure 3(b), the power required decreased by almost 40% from hover to an advance ratio close to unity, which is phenomenal for an MAV-scale rotor. A twin-cyclocopter ( Figure 1) has five control degrees of freedom (three RPMs and two thrust directions).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Systematic forward flight studies were also conducted in the wind tunnel, which showed the potential for a cyclorotor to perform efficient high-speed forward flight even beyond an advance ratio of 1.0 by a simple phasing of the cyclic blade-pitch schedule. 6,14 As shown in Figure 3(b), the power required decreased by almost 40% from hover to an advance ratio close to unity, which is phenomenal for an MAV-scale rotor. A twin-cyclocopter ( Figure 1) has five control degrees of freedom (three RPMs and two thrust directions).…”
Section: Introductionmentioning
confidence: 74%
“…Pioneering research on the cyclorotor concept for MAV applications has been conducted over the last 10 years. [4][5][6][7][8][9][10][11][12][13][14][15][16] This body of work represents one of the most comprehensive evaluations ever conducted on cyclorotors at MAV scales and involved systematic performance measurements in both hover 4,[8][9][10][11] and in a wind tunnel, [12][13][14] flowfield studies using particle image velocimetry (PIV), 4,8,9 computational fluid dynamic analysis, 12,13 and aeroelastic modeling. 15 These studies established a fundamental understanding of the cyclorotor performance and helped in formulating a set of design principles for an efficient cyclorotor operating at MAV-scale Reynolds numbers (Re < 40,000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by changing the pitching angle of the blades and controlling the rotational speed, the propulsive jet can be instantaneously controlled in terms of magnitude and direction, providing higher maneuverability and controllability to the aircraft [14]. Moreover, since cycloidal rotors operate at much lower rotational speeds than conventional propellers do, they produce considerably lower levels of noise [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Cycloidal rotors have been studied for their application in vertical-axis wind and water turbines (Hwang et al , 2009; Maître et al , 2013; El-Samanoudy et al , 2010; Islam et al , 2008). Recent studies also investigated their application in unmanned micro aerial vehicles (Jarugumilli et al , 2014; Benedict et al , 2014, 2013, 2011; Benedict, 2010; Yun et al , 2007; Iosilevskii and Levy, 2006; Shrestha et al , 2014). Nowadays, their commercial use is limited to wind turbines and marine propellers.…”
Section: Introductionmentioning
confidence: 99%